A Topotactic Synthetic Methodology for the Synthesis of Nanosized MFI Zeolites with Hierarchical Structures. Issue 48 (24th July 2018) - Li, Ang; Wang, Xue; Wang, Tao; Liu, Huali; Gao, Tunan; Fan, Meihong; Huo, Qisheng; Qiao, Zhen‐An
Abstract: Much effort has been invested in the designed synthesis of zeolites with nanosized and hierarchical structures in recent decades, on account of increasing demands in practical applications, especially catalysis. Herein, a new topotactic synthetic strategy is demonstrated to synthesize nanosized and hierarchical zeolites in a one‐step procedure. By using silica spheres as the adjustable amorphous precursors and tetrapropylammonium hydroxide as a structure‐directing agent, effortless control of both size and porosity can be achieved in this system with no extra templates. With a simple hydrothermal process, hierarchical zeolite spheres can be modified with acid cites (Al species incorporated in the framework). Benefitting from its mesoporosity, palladium nanoparticles are incorporated into the nanosized hierarchical zeolite, which makes the materials suitable for use in a cascade catalysis reaction of benzimidazole derivatives, including independent acid catalysis and hydrogenation sites. The nanocomposites show exceptional activity and stability in catalysis and recycling reaction. This strategy can be developed into other versatile and practicable scaffolds for advanced zeolite catalytic nanoreactor systems. Abstract : Filling the gaps : A topotactic synthetic methodology allows the synthesis of nanosized hierarchical MFI zeolite spheres and particles from silica spheres and tetrapropylammonium hydroxide (TPAOH; see figure). Dissolved silica species rebond around TPA + and zeolite structures are generated with defective mesoporous walls as a result of desilication of the initial silica spheres. Upon further crystal growth, zeolite nanoparticles can be obtained.